Estudio Para Establecer La Frecuencia De Presentación De Cristales En Caninos Y Felinos De La Clínica De La Universidad Antonio Nariño Entre Los Años 2017 Al 2019 (2023)
This research compiles representative data of the different types of crystals that can occur in the urinary tract, allowing us to delve deeper into the frequency of presentation in the canine and feline population that developed the deposit of minerals during the study period (2017 to 2019). , articles such as “Animal model of naturally occurring stone disease” (Alford et al., 2020), “Paradigm Changes in the Role of Nutrition for the Management of Canine and Feline Urolithiasis” (Osborne et al., 2008) and “Urolithiasis canine and retrospective study of its casuistry at the Veterinary Hospital of the University of Zaragoza” (Gil, S., 2016) mention percentages of studies of the presentation of crystals, however, it does not mention a detailed and updated study of the frequency of presentation In colombia .